2011
DOI: 10.1186/1750-1172-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphatase deficiency

Abstract: Glucose-6-phosphatase deficiency (G6P deficiency), or glycogen storage disease type I (GSDI), is a group of inherited metabolic diseases, including types Ia and Ib, characterized by poor tolerance to fasting, growth retardation and hepatomegaly resulting from accumulation of glycogen and fat in the liver. Prevalence is unknown and annual incidence is around 1/100,000 births. GSDIa is the more frequent type, representing about 80% of GSDI patients. The disease commonly manifests, between the ages of 3 to 4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
2
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(177 citation statements)
references
References 121 publications
(159 reference statements)
2
159
2
14
Order By: Relevance
“…As a result, we found that patients with GSD type Ib reported lower values than type Ia. This can be explained clinically since GSD Ib subjects often suffer from frequent infections and bowel disease, which can affect everyday living (Froissart et al 2011). However, interestingly, in our cohort, we found a lower rate of IBD than that in the ESGSD study (18 % vs. 77 %) (Visser et al 2002).…”
Section: Discussionmentioning
confidence: 40%
“…As a result, we found that patients with GSD type Ib reported lower values than type Ia. This can be explained clinically since GSD Ib subjects often suffer from frequent infections and bowel disease, which can affect everyday living (Froissart et al 2011). However, interestingly, in our cohort, we found a lower rate of IBD than that in the ESGSD study (18 % vs. 77 %) (Visser et al 2002).…”
Section: Discussionmentioning
confidence: 40%
“…[37][38][39][40] Liver transplant (LT) or a combined liver and kidney transplant is needed in some cases. [41][42][43] Menorrhagia appears to be a problem in females of reproductive age with GSD I. 44,45…”
Section: Clinical Historymentioning
confidence: 99%
“…Anemia, bleeding tendency, diarrhea, and late onset puberty are other common findings. Patients especially with poor metabolic control have long-term complications such as short stature, developmental delay, seizures, intellectual disability, hepatic adenoma, renal dysfunction, gout and osteoporosis 5 . Frequent meals, continuous nocturnal drip-feeding and the administration of uncooked cornstarch are the treatment modalities commonly used either alone or in combination 6 .…”
mentioning
confidence: 99%